Studies of the impact on alcohol control in case of joining Comprehensive and Progressive Agreement of Trans-Pacific Partnership (CPTPP) - Vongsirisopak, Sirikul (Disease Control Journal, 2021)
Comprehensive and Progressive Agreement of Trans-Pacific Partnership or CPTPP is a new generation of free trade and investment agreement which extensively includes many aspects on trade, services, and investment in order to establish common standards and regulations among the member states. Its wide scope and extensive matters involved many relevant issues further than the existing trade agreement previously done by Thailand. Regarding the national control measures on alcoholic beverages, the alcoholic beverages are non-ordinary commodities that harmful to health and lead to adverse consequences to families, communities, and societies as a whole However, under this new generation agreement, the alcoholic beverages have been included as general commodities which create a potential conflict perspective between trade and health policies — proposed commercial benefits of free trade or existing policies on public health protection. With regard to the government’s intention to join this agreement, it is necessary to have an analysis and synthesize study on the impact of CPTPP on Thailand alcohol control laws or policies. We conducted a documentary research through relevant information, technical papers, and research documents that can be accessed online. Findings reveal that 7 chapters of CPTPP may have adverse impact on alcohol control policies in Thailand which includes chapter 8 technical barriers to trade, chapter 9 investment, chapter 10 cross-border trade in services, chapter 14 electronic commerce, chapter 18 intellectual property, chapter 25 regulatory coherence, and chapter 28 dispute settlement. After being a party to CPTTP, Thailand will have to amend the domestic laws to be in accordance with this agreement. As a result, the alcohol control policies for protecting the health of Thai people will be weakened, and gaps on health policies could be interfered by international affairs. The negotiations in order to join the CPTPP should be considered comprehensively through sufficient and adequate information and should deliver the most benefit to the public. Additionally, recovery policy for affected people should be promptly provided.